Mortality rates due to Bladder cancer in Iran during 2001-2007: A national cancer registry-based study - Maryam Khayamzadeh (Men's Health Journal, 2019)
Introduction: Bladder cancer is the ninth common cause of cancers in both sexes worldwide. Nevertheless, little is known about the descriptive and analytic epidemiology of bladder cancer in Iran. The present study aimed to describe the nationwide distribution of death due to bladder cancer in Iran.